A MORPHOLOGICAL ANALYSIS OF THE FRENCH COLONIAL ARCHITECTURE IN ALGERIA: THE FACADES OF BISKRA - BELAKEHAL, A; BOUSSORA, K; FARHI, A; SRITI, L (Courrier du Savoir; Vol. 20 (2015): COURRIER DU SAVOIR, 2016)
The analysis of these dwellings facades, constructed during the French colonial era in Biskra, an Algerian southern town, aims to identify not only the characteristics of this largely mistreated architectural heritage, but also, to grasp the co-occurrence of its morphological characteristics. Hence, a morphological approach was applied to a representative corpus of 190 facades located in the centre of this town. In order to conduct such an analysis, a model of the façade consisting on an elementary mesh of solid and void (a window network) was elaborated. This model allows various operations of segmentations through the observation of discontinuities, namely lyses. These latter define the composition levels (primary structuring) and the openings’ sequences (secondary structuring). The combinations of composition levels and spans arrangement produce a particular organisation for this windowed network, which was examined in detail, in this study. The outcomes from the studied corpus give prominence to both the delimited levels through the horizontal lyses (primary structuring) and the definition of the spaced out spans (secondary structuring). They also allows the description of the façades studied as having a simple character,  denoted by a variety of elements, connected  arbitrarily and  organized into one or more levels of composition. Moreover, these results suggest, that the renewal of the building stock in this old colonial city centre, could be done in respect to the models of the horizontal lyses structuring with either the introduction of new architectural elements, such as windows, balconies and arches, or the re-use of the forms of the existing ones. It is important to mention here, that the outcomes of this research can also help in different works and actions aiming to restore the old buildings stock within the area studied. A protected sector plan is the most suitable framework for such actions according to Algerian planning regulation. Finally, this research has demonstrated that some of the façades studied shared a homogeneous character, whereas others are different, they neither share the same stylistic elements, nor do they share the same structuring models. This result needs a further research, not only to explain the origin of these disparities within the corpus, considering the geographical localization of the façade in this colonial city centre (the cadastral section), but also, to explore some extrinsic factors, in order to interpret and explain the morphological characteristics of these dwellings façades in Biskra city centre, during the French colonial era.